Effects of Growth Hormone on Cardiac Remodeling During Resistance Training in Rats - Adriana Junqueira; Antônio Carlos Cicogna; Letícia Estevam Engel; Maiara Almeida Aldá; Loreta Casquel de Tomasi; Rogério Giuffrida; Inês Cristina Giometti; Ana Paula Coelho Figueira Freire; Andreo Fernando Aguiar; Francis Lopes Pacagnelli (Arquivos Brasileiros de Cardiologia, 2015)
Abstract Background: Although the beneficial effects of resistance training (RT) on the cardiovascular system are well established, few studies have investigated the effects of the chronic growth hormone (GH) administration on cardiac remodeling during an RT program. Objective: To evaluate the effects of GH on the morphological features of cardiac remodeling and Ca2+ transport gene expression in rats submitted to RT. Methods: Male Wistar rats were divided into 4 groups (n = 7 per group): control (CT), GH, RT and RT with GH (RTGH). The dose of GH was 0.2 IU/kg every other day for 30 days. The RT model used was the vertical jump in water (4 sets of 10 jumps, 3 bouts/wk) for 30 consecutive days. After the experimental period, the following variables were analyzed: final body weight (FBW), left ventricular weight (LVW), LVW/FBW ratio, cardiomyocyte cross-sectional area (CSA), collagen fraction, creatine kinase muscle-brain fraction (CK-MB) and gene expressions of SERCA2a, phospholamban (PLB) and ryanodine (RyR). Results: There was no significant (p > 0.05) difference among groups for FBW, LVW, LVW/FBW ratio, cardiomyocyte CSA, and SERCA2a, PLB and RyR gene expressions. The RT group showed a significant (p < 0.05) increase in collagen fraction compared to the other groups. Additionally, the trained groups (RT and RTGH) had greater CK-MB levels compared to the untrained groups (CT and GH). Conclusion: GH may attenuate the negative effects of RT on cardiac remodeling by counteracting the increased collagen synthesis, without affecting the gene expression that regulates cardiac Ca2+ transport.